التعليم الثانوي في محافظة كربلاء المقدسة تشخيص ومعالجة (Journal of the College of Basic Education, 2020)
Education (and particularly secondary education ) has a great important in developing and building societies . secondary education is beneficial in determine the future character of the learners . the problem of this research can be stated in the following question : what the problem that the venality of secondary education ?what the problem that the secondary education face ?what is the future vision that could change the reality of teaching ? the researcher utilizes the description methodology . the community of this research consists of all the secondary school in the province of karbala .the sample of this research is the whale community . A question was utizies as a tool of this paper after achieving its validity and reliability . The question consists of eight aspects stated as follows:1.Schad building which consists of (9)items.2,Equipmentg which Consists of (11) items.3. The stalemates and parents which Consists of (13)items. 4.The school Staff which consists of (11) items .5.Curriculum which consists of (12) items .6. Educational Supervision which consists of (12) items. 7.The school Principles consists of (10) items ,and .8. The educational guides of (11) items. After collecting data ,it is Statistiscally processed by using the mean and the percentage .The results reveal that the Secondary education in Karbala is weak . The researcher interpret the first quarter of the items of each aspect .The researcher determines the reality of Secondary education with (48) points. The researcher recommended a future vision of (51)items and some Suggestions that may serve the reality of Education in Karbalaa and Iraq.